(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Barley is an expensive crop. According to the data provided by FAO in 2020, the area of barley was 55.7 million ha, and the yield was 24.4 s/ha. Barley is distributed and cultivated in most regions of the world. It is grown everywhere from cold regions, deserts, semi-deserts, mountainous regions, for example, Tibet, Pamir, Caucasus. Barley is widely cultivated in Central Asian countries, including Uzbekistan. It contains antibiotics, vitamins, proteins, trace elements, mineral salts, enzymes, amino acids. Most of these are important antibiotics and vitamins. Barley plant is divided into spring and autumn barley types depending on the period of planting. In Uzbekistan, spring tradition yields 4-7 s/ha in dry farming and 35-40 s/ha in water. Autumn barley is common in irrigated lands. It is mainly grown as fodder and cereal crops. In the national economy, barley is used as a raw material for the beer industry due to the low content of food, feed, and protein in its grain for various purposes.